2019
DOI: 10.1098/rspb.2019.1520
|View full text |Cite
|
Sign up to set email alerts
|

Plant–soil–foliage feedbacks on seed germination and seedling growth of the invasive plant Ageratina adenophora

Abstract: Some exotic plants become invasive because they partially release from soil-borne enemies and thus benefit from positive plant–soil feedbacks (PSFs) in the introduced range. However, reports that have focused only on PSFs may exaggerate the invader's competitiveness. Here, we conducted three experiments to characterize plant–soil–foliage feedbacks, including mature leaves (ML), leaf litter (LL), rhizosphere soil (RS) and leaves plus soil (LS), on the early growth stages of the invasive plant Agerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…[31], Passalora ageratinae [32], Alternaria alternata [33], and Collectotrichum [34,35]. In recent, our group has indicated that the foliar fungi from family Didymellaceae are adverse to the growth of A. adenophora [36], and these fungi frequently occurs in the surrounding environment, such as in the withered leaves and the canopy air of hosts [37]. In this study, two experiments were designed to verify the expectation above.…”
Section: Introductionmentioning
confidence: 67%
“…[31], Passalora ageratinae [32], Alternaria alternata [33], and Collectotrichum [34,35]. In recent, our group has indicated that the foliar fungi from family Didymellaceae are adverse to the growth of A. adenophora [36], and these fungi frequently occurs in the surrounding environment, such as in the withered leaves and the canopy air of hosts [37]. In this study, two experiments were designed to verify the expectation above.…”
Section: Introductionmentioning
confidence: 67%
“…The vertically transmitted pathogens alone seem to suggest a declining adverse effect on the growth of A. adenophora over time and thus may positively contribute to A. adenophora expansion; in contrast, the increased virulence of the horizontally transmitted pathogens seems to slow and eventually stop plant invasion. However, our previous report indicated that foliar microbes, primarily fungi, in older sites produce stronger adverse effects on the growth of A. adenophora than do those in younger sites [38]. Although the horizontally transmitted fungal pathogens showed, on average, a lower virulence to A. adenophora than the vertically transmitted pathogens (Fig 5A ), the horizontally transmitted fungi may overwhelm the vertically transmitted fungi in the growth performance of A. adenophora.…”
Section: Plos Pathogensmentioning
confidence: 78%
“…Escaping or encountering less virulent specialists if not escaping (Reinhart et al 2010) (Vandegrift et al 2015) are important to plant invasions. In this case, these specialists of seedborne fungal pathogens are not easy to escape; however, their decreased virulence may not directly contribute to A. adenophora invasion because the foliar fungi as a whole in older sites produce stronger adverse effects on the growth of A. adenophora than do those in younger sites (Fang et al 2019a). Therefore, similar the virulence evolution of non-SPs, the evolution of decreased virulence of SPs may also be in response to the increased density of A. adenophora, as models predict that low-virulence strains prevail, and vertical transmission becomes more prevalent, when host density increases if parasites are transmitted both vertically and horizontally on a host (Lipsitch et al 1996).…”
Section: Discussionmentioning
confidence: 99%